اسلام اور عیسائیت کے تصور نکاح کا تقابلی جائزہ (Al-Qamar, 2023)
Marriage is a legally and socially sanctioned union, usually between a man and a woman. It is a social ceremony that is continued in every religion of the world, in every region and in every nation, because it is related to the survival and continuity of life, which if left, the human race will be cut off. Christians believe that marriage is a gift from God. In Islam, marriage holds great value and importance. Islam and Christianity, both Semitic religions, have some commonalities regarding the concept of marriage. In both Islam and Christianity, the importance of marriage is emphasized, some relationships are forbidden for marriage and there are severe punishments for those who marry with mahrams. In both religions, certain conditions of marriage are necessary to fulfil. In both religions, the husband is declared as the ruler and administrator, and it is ordered to treat their wives with love, compassion and gentleness. We found some differences regarding marriage affairs. Unlike Islam, celibacy is permitted and encouraged in Christianity. Islam allows a man to have up to four wives at the same time while Christianity allows only one marriage. In Islam, there is a clear concept of haqq-e-mahr, while in Christianity there is no such concept. This article presents a comparative study of the concept of marriage in Islam and Christianity.
Keywords: Islam; Christianity; concept of marriage; teachings; commonalities; differences